ANALISIS KONSEP SHAFQATAINI FI SHAFQATIN PADA HYBRID CONTRACT AKAD IJARAH MUNTAHIYA BIT TAMLIK (IMBT) - Primadhany, Erry Fitrya (Journal Evidence Of Law, 2023)
The hybrid contract provides benefits for Islamic banks and customers. By combining two types of contracts, the parties involved in the transaction can maximize the generated profits. For example, in the ijarah muntahiya bit tamlik contract, two contracts are combined, namely the ijarah (leasing) contract and the sale and purchase contract, allowing the asset owner to sell the asset to the customer at the end of the lease period. There is a debate regarding the permissibility of multiple contracts based on some hadiths of the Prophet. For instance, the hadith regarding the prohibition of combining two transactions in one. Therefore, the use of hybrid contracts in Islamic financial transactions needs to be thoroughly examined to ensure compliance with Sharia principles and not violate Islamic law. This research is a type of normative legal research that examines Islamic legal norms, principles, and relevant doctrines related to the study's theme. The approach used is a conceptual approach intended to analyze concepts within Islamic law to understand their meanings. The hybrid contract in the Sharia-compliant banking product ijarah muntahiya bit tamlik is a permissible contract according to Sharia. In the Ijarah Muntahiya Bit Tamlik transaction, there are factors that underlie the absence of combining two transactions, namely the factor of the same time frame. The implementation of time in Ijarah Muntahiya Bit Tamlik is not simultaneous but gradual. Thus, the Ijarah Muntahiya Bit Tamlik transaction is valid. Furthermore, the permissibility of this transaction is based on considerations of maslahah (public interest), including eliminating difficulties in society, especially in the economic field